2020
DOI: 10.1038/s41467-020-15239-3
|View full text |Cite
|
Sign up to set email alerts
|

Plant Raf-like kinases regulate the mRNA population upstream of ABA-unresponsive SnRK2 kinases under drought stress

Abstract: SNF1-related protein kinases 2 (SnRK2s) are key regulators governing the plant adaptive responses to osmotic stresses, such as drought and high salinity. Subclass III SnRK2s function as central regulators of abscisic acid (ABA) signalling and orchestrate ABA-regulated adaptive responses to osmotic stresses. Seed plants have acquired other types of osmotic stress-activated but ABA-unresponsive subclass I SnRK2s that regulate mRNA decay and promote plant growth under osmotic stresses. In contrast to subclass III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
164
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(170 citation statements)
references
References 51 publications
5
164
0
1
Order By: Relevance
“…ABA also enables the activation of guard cell membrane-localized transporters through phosphorylation mediated by calcium dependent kinases (CDPKs) and other kinases, indicating alternative stomatal regulatory pathways independent of SnRK2s (Cai et al, 2017;Pornsiriwong et al, 2017). Most recently, subgroup B Raf-like kinases have been identified as upstream regulators of SnRK2s for ABA signal transduction and response to osmotic and drought stresses in Arabidopsis (Saruhashi et al, 2015;Katsuta et al, 2020;Lin et al, 2020;Soma et al, 2020;Takahashi et al, 2020). Furthermore, it's revealed that this regulatory module is evolutionarily conserved in land plants, at least for conferring protection against drought (Katsuta et al, 2020).…”
Section: Overview Of Aba Signaling Networkmentioning
confidence: 99%
“…ABA also enables the activation of guard cell membrane-localized transporters through phosphorylation mediated by calcium dependent kinases (CDPKs) and other kinases, indicating alternative stomatal regulatory pathways independent of SnRK2s (Cai et al, 2017;Pornsiriwong et al, 2017). Most recently, subgroup B Raf-like kinases have been identified as upstream regulators of SnRK2s for ABA signal transduction and response to osmotic and drought stresses in Arabidopsis (Saruhashi et al, 2015;Katsuta et al, 2020;Lin et al, 2020;Soma et al, 2020;Takahashi et al, 2020). Furthermore, it's revealed that this regulatory module is evolutionarily conserved in land plants, at least for conferring protection against drought (Katsuta et al, 2020).…”
Section: Overview Of Aba Signaling Networkmentioning
confidence: 99%
“…Both the positive and the negative regulatory proteins of the SnRK2 kinase are, too, conserved throughout land plant evolution ( Lind et al, 2015 ; Saruhashi et al, 2015 ; Yasumura et al, 2015 ; Stevenson et al, 2016 ; Lin et al, 2020 ; Takahashi et al, 2020 ). Post-translational modifications and protein–protein interactions are the two key regulation means of SnRK2 ( Belin et al, 2006 ; Vlad et al, 2009 ; Soon et al, 2012 ; Saruhashi et al, 2015 ; Stevenson et al, 2016 ; Nguyen et al, 2019 ; Lin et al, 2020 ; Soma et al, 2020 ; Takahashi et al, 2020 ). The activation of Arabidopsis SnRK2s requires phosphorylation of key serine residues in kinase activation loop (Ser171 and Ser175 for AtSnRK2.6/OST1; Vlad et al, 2010 ; Soon et al, 2012 ).…”
Section: The Pp2c-snrk2 Signaling Module Throughout Plant Evolutionmentioning
confidence: 99%
“…The core ABA signaling pathway has been reconstituted successfully with those key components in vitro [ 35 ]. Interestingly, several recent studies simultaneously showed that Raf-like kinases (RAFs) could quickly activate SnRK2s to respond to ABA, osmotic and drought stress by direct phosphorylation [ 36 , 37 , 38 , 39 ].…”
Section: Mediator Complex As a Pivotal Regulator Of Aba Signaling mentioning
confidence: 99%